Pengaruh modal psikologi dan pemberdayaan terhadap kinerja guru dengan mediasi kepuasan kerja - Novitasari, Dyah Pitaloka; Bambang Suko Priyono (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Performance is a determinant of achieving the goals of an organization's success. Organizational performance will be maximized when the organization is able to manage employees within the organization. This research aims to find out the psychological capital’s influence and empowerment on performance of teacher by mediating job satisfaction. The study was conducted on 112 teachers at SMK Negeri 1 Bawen Semarang Regency with total sampling method. The variables studied were independent variables, namely psychological capital and empowerment, the mediating variable was job satisfaction and the dependent variable was teacher performance. This study used multiple regression analysis in analizing data. Results of the study are obtained: 1) Psychological capital has a positive and significant effect on teacher job satisfaction (2) Empowerment has a positive and significant effect on teacher job satisfaction. (3) Psychological capital has a positive and significant effect on performance of teacher (4) Empowerment has a positive and significant effect on performance of teacher. (5) Job satisfaction has a positive and significant effect on performance of teacher. (6) Empowerment has the greatest influence compared to psychological capital on performance of teacher. (7) Job satisfaction mediates the effect of psychological capital on performance of teacher.(8) Job satisfaction mediates the effect of empowerment on performance of teacher.